Students’ Perceptions of Reciprocal Teaching in Reading Comprehension Class - Surahmat Agus Munandar; Aminah Aminah; Muhammad Ahkam Arifin (Tamaddun Life, 2020)
This research aimed to find out the difficulties and the benefits of reciprocal teaching perceived by the students in reading comprehension class, and the strategy in reciprocal teaching that the students prefer the most. This research was qualitative research applying phenomenological approach. The participants of this study were 5 students majoring in English Education Department of Institute Parahikma Indonesia. The data was collected by using semi-structured interview and it was analyzed by using thematic analysis adapted from Given (2018). The result of this study indicated that the difficulties faced by the students are less teacher’s monitoring, students’ interest in learning reading comprehension which makes them bored, self-competence of the students in understanding the text, and the difficulty in unifying their perceptions. The benefits of it that the students perceived are that they become more creative and imaginative, and it is an encouraging method and effective. Furthermore, it can boost their enthusiasm and create collaborative engagement. However in term of the most preferred strategies in reciprocal teaching, most of the students perceived that questioning is the best.